Evaluasi Sistem Informasi Pemesanan Tiket Pesawat Berbasis Website pada Mmbc Travel Menggunakan Metode TAM (Technology Acceptance Model) - Durra Nabila; Qori Haimatul Hidayah (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2026)
This study aims to assess the level of user acceptance of the website-based airline ticket booking system at MMBC Travel using the Technology Acceptance Model (TAM). The TAM model is used to measure the influence of the variables Perceived Ease of Use, Perceived Effectiveness, Attitude Toward Use, and Behavioral Intention to Use on user acceptance of the system. Data were obtained by distributing questionnaires to 100 respondents who were active users of the system. Data analysis was conducted using path analysis to examine the relationships between the variables in the model. The results showed that all relationships between the tested variables had a positive and significant impact. The average user perception score was above 3.5 on a scale of 5, indicating that the information system was considered quite easy to use, useful, and well-received by users. Therefore, it can be concluded that the website-based airline ticket booking system at MMBC Travel meets the aspects of ease of use and usefulness, making it worthy of continued use and development.